Efektivitas Eksekusi Lelang Hak Tanggungan - Gegana, Reza Pramasta; Sanata, Kalen; Ramadoni, Sofwan Rizko (Jurusan Pendidikan Ilmu Pengetahuan Sosial FKIP Universitas Mulawarman, 2023)
This research is a type of qualitative research with research operationalization using a natural paradigm. Primary data and secondary data are analyzed qualitatively. Then the data that has been collected is processed, qualified and linked systematically to obtain a conclusion regarding the answer to the problem being studied. The results of the research in its implementation found obstacles, among other factors, law enforcers who were not thorough and careful in carrying out their duties. This typo could be something like typing the certificate number, owner's name, etc. This error will become problematic when there are many files to be submitted for auction. The large number of incoming files will become an obstacle and make the auction process take longer. Facilities and infrastructure constraints factor, the bank does not advertise intensively, it is small and more than modest. Community Factors: In carrying out the mortgage rights auction execution, some people still think that this auction execution is not considered a solution to a problem.